The Role of History of Photosynthesis on Preservice Biology Teachers’ Scientific Literacy Skill - Listiani; Rara Amalina Qisthina; Sri Gusriyanti Putri (Universitas Pendidikan Ganesha, 2025)
The history of science plays an important role in science teaching and learning. This is because the history of science consists of meaningful information related to scientific processes and concepts. This study implemented a historical episode of photosynthesis discovery conducted by Ingenhousz as a learning resource for learning photosynthesis. A single case study was implemented in this research aimed at finding the role of the history of science in student understanding of science concepts and scientific literacy skills of preservice Biology teachers. The data was collected through summative evaluation tests, interviews, and document collection. The results show that the preservice biology teachers understand photosynthesis concepts and scientific literacy in all dimensions. Therefore, it can be concluded that the history of photosynthesis discovery contributes positively to preservice Biology teachers’ understanding of photosynthesis concepts and scientific literacy.